Banks During the Argentine Crisis : Were they All Hurt Equally? Did they All Behave Equally? - Juan-Ramon, V.; Barajas, Adolfo; Basco, Emiliano; Quarracino, Carlos (Washington, D.C. : International Monetary Fund, 2006)
The simple answer to both questions in the title of this paper is: No. We concentrate on the three main risk elements that contributed to the banking system's difficulties during the crisis: increasing dollarization of the balance sheet, expanding exposure to the government, and, eventually, the run on deposits. We find that there was substantial cross-bank variation in these elements-that is, not all banks were hurt equally by macroeconomic shocks. Furthermore, using panel data estimation for the 1998-2001 period, we find that depositors were able to distinguish high- from low-risk banks, and that individual banks' exposure to currency and government default risk depended on bank fundamentals and other characteristics. Thus, not all banks behaved equally in the run-up to the crisis. Finally, our results have implications for the existence of market discipline in periods of stress and for banking regulation, which may have led banks to underestimate some of the risks they incurred.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet